Provision of a comprehensive medicines review is associated with lower mortality risk for residents of aged care facilities: a retrospective cohort study. (7th July 2022) - Sluggett, Janet K; Caughey, Gillian E; Air, Tracy; Moldovan, Max; Lang, Catherine; Martin, Grant; Carter, Stephen R; Jackson, Shane; Stafford, Andrew C; Wesselingh, Steve L; Inacio, Maria C
Abstract: Background: no studies have examined the impact of residential medication management review (RMMR, a 24-year government subsidised comprehensive medicines review program) in Australian residential aged care facilities (RACFs) on hospitalisation or mortality. Objective: to examine associations between RMMR provision in the 6–12 months after RACF entry and the 12-month risk of hospitalisation and mortality among older Australians in RACFs. Design: retrospective cohort study. Subjects: individuals aged 65–105 years taking at least one medicine, who entered an RACF in three Australian states between 1 January 2012 and 31 December 2015 and spent at least 6 months in the RACF ( n = 57, 719). Methods: Cox regression models estimated adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) for associations between RMMR provision and mortality. Adjusted subdistribution hazard ratios were estimated for associations between RMMR provision and next (i) emergency department (ED) presentation or unplanned hospitalisation or (ii) fall-related ED presentation or hospitalisation. Results: there were 12, 603 (21.8%) individuals who received an RMMR within 6–12 months of RACF entry, of whom 22.2% (95%CI 21.4–22.9) died during follow-up, compared with 23.3% (95%CI 22.9–23.7) of unexposed individuals. RMMR provision was associated with a lower risk of death due to any cause over 12-months (aHR 0.96, 95%CI 0.91–0.99), but was not associated with ED presentations or hospitalisations for unplanned events or falls. Conclusions: provision of an RMMR in the 6–12 months after RACF entry is associated with a 4.4% lower mortality risk over 12-months but was not associated with changes in hospitalisations for unplanned events or falls.